West Africa during the Atlantic slave trade : archaeological perspectives - DeCorse, Christopher R. (London ; New York : Bloomsbury, 2016)
Surveying archaeological data from West Africa, with sites ranging from the Senegambia to the Cameroon, this volume focuses on data from about 1500, a time period that witnessed dramatic transformations in African political and social life.
Tools for understanding transformation and continuity in Senegambian society : 1500-1900 / Susan Keech McIntosh, with a contribution by I. Thiaw -- Historical process and the impact of the Atlantic trade on Banda, Ghana, c. 1800-1920 / Ann Brower Stahl -- The effect of the slave trade on the Bassar ironworking society, Togo / Philip Lynton de Barros -- Change and continuity in coastal Bénin / Kenneth G. Kelly -- Kanem-Borno : a brief summary of the history and archaeology of an empire of the central bilad al-sudan / Detlef Gronenborn -- State formation and enslavement in the southern Lake Chad basin / Scott MacEachern -- 500 years in the Cameroons : making sense of the archaeological record / Augustin F.C. Holl -- An Americanist perspective on African archaeology : toward an archaeology of the Black Atlantic / Theresa A. Singleton.
Online resource; title from PDF title page (EBSCO, viewed September 1, 2016).
Includes bibliographical references and index.
eBooks on EBSCOhost
Keywords: Excavations (Archaeology) -- Africa, West; Africa, West -- Antiquities; Slave trade -- Africa, West; Fouilles (Archéologie) -- Afrique occidentale; Traite des esclaves -- Afrique occidentale; HISTORY -- Africa -- West; Antiquities; Excavations (Archaeology); Slave trade; West Africa